312 Female sex independently predicts adjuvant immunotherapeutic benefit from CTLA4 immune checkpoint inhibition. (9th November 2020) - Tarhini, Ahmad; Kang, Ni; Lee, Sandra; Stephen Hodi, F; Cohen, Gary; Hamid, Omid; Hutchins, Laura; Sosman, Jeffrey; Kluger, Harriett; Eroglu, Zeynep; Koon, Henry; Lawrence, Donald; et al.
Abstract : Background: Sex differences in tumor immunity and response to immunotherapy were shown in murine models and descriptive analyses from recent clinical trials. Female sex hormones have been implicated in melanoma development and response to systemic therapy. We hypothesized a gender difference in response to adjuvant immunotherapy with ipilimumab (3 or 10 mg/kg; ipi3 or ipi10) versus high dose IFNα (HDI) as tested in the E1609 trial. Methods: E1609 demonstrated significant overall survival (OS) benefit with ipi3 versus HDI. 1 We investigated treatment efficacy between ipi and HDI in the subgroups by sex (female, male), age (< 55 or ≥55), stage at study entry (IIIB, IIIC, M1a/1b), ECOG performance status (PS 0, 1), ulceration (yes, no), primary tumor (known, unknown), number of lymph nodes involved (0, 1, 2–3, 4+). Forest plots were created to compare OS and RFS with ipi3 vs. HDI and ipi10 vs. HDI using the concurrently randomized ITT populations. For the estimated HRs, 95% confidence intervals were created for all subgroups. Results: The subgroups of female, stage IIIC, PS=1, ulcerated, in-transit without lymph node involvement demonstrated significant improvement in overall survival (OS) and/or relapse free survival (RFS) with ipi3 versus HDI as summarized in table 1. Female sex was significant for both OS and RFS and was further explored. In investigating RFS with ipi3 versus HDI, a multivariate Cox regression model including sex, treatment and interaction term of sex*treatment, indicated a significant interaction between sex and treatment (P = 0.026). Including sex, PS (0 vs. 1), age (<55 vs. 55+), ulceration (yes vs. no), stage (IIIB, IIIC, M1a, M1b), treatment and interaction term of sex*treatment, indicated a significant interaction between sex and treatment (P = 0.024). While similar trends were seen, no significant interactions between sex and treatment effect were found in the OS multivariate analysis or in the comparison of ipi10 versus HDI. When exploring age, in the univariate analyses in the ipi3 versus HDI comparison older women appeared to drive most of the difference (age ≥55: OS, P=0.02 and RFS, P=0.08; differences non-significant for women <55). Table 1. Conclusions: Female sex was independently associated with RFS adjuvant immunotherapeutic benefit from ipi3, supporting a potentially important role for female related factors in the immune response against melanoma, and these warrant further investigation. Trial Registration: NCT01274338 Ethics Approval: The study protocol was approved by the institutional review board (IRB) of each participating institution and conducted in accordance with Good Clinical Practice guidelines as defined by the International Conference on Harmonisation. This study was monitored by the ECOG-ACRIN DataSafety Monitoring Committee and the NCI. Consent: All patients provided IRB-approved written informed consent. Reference: Tarhini AA, Lee SJ, Hodi FS, Rao UNM, Cohen GI, Hamid O, Hutchins LF, Sosman JA, Kluger HM, Eroglu Z, Koon HB, Lawrence DP, Kendra KL, Minor DR, Lee CB, Albertini MR, Flaherty LE, Petrella TM, Streicher H, Sondak VK, Kirkwood JM. Phase III Study of Adjuvant Ipilimumab (3 or 10 mg/kg) Versus High-Dose Interferon Alfa-2b for Resected High-Risk Melanoma: North American Intergroup E1609. J Clin Oncol . 2020 Feb 20;38(6):567–575. PMID: 31880964.